PENINGKATAN KOMPETENSI KOMUNIKASI MASYARAKAT DESA KOTO SENTAJO DALAM MEWUJUDKAN WISATA BUDAYA RUMAH GODANG DI KABUPATEN KUANTAN SINGINGI – RIAU - Genny Gustina Sari; Chelsy Yesicha; Yohannes Firzal (Swadaya: Indonesian Journal of Community Empowerment, 2019)
Riau Province Leading Tourism Village Planning in 2015 from the Riau Province Creative and Tourism Economy Office (2015: 210) explained that the analysis to determine the leading tourism village in the study was carried out in two stages. the first stage, the data shows that basically has a positive response to the development of tourism activities in all prospective tourist villages (15 villages). The analysis showed that the majority of respondents expressed their agreement if the village area was made into a rural tourism area. In the second stage, the results of the field survey data assessment showed four (4) selected villages that have the highest value in terms of potential, affordability, availability of facilities, and the variety of activities that can be carried out by tourists. One of them is Koto Sentajo Village, Sentajo Raya District, Kuantan Singingi Regency. Kuantan Singingi Culture has a very exotic sale value in 2017 Kuantan Singingi Culture is included in the National Strategic Tourism Area (KSPN) and is included as a major cultural tourism destination in Riau. Efforts to improve the competency of the tourism village community in Koto Sentajo include public speaking training, village web creation training, tour guide training and e-commerce training. Keywords: Increased communication competence, village tourism, training.